Possible influence of the warm pool ITCZ on compound climate extremes during the boreal summer. (2nd November 2021) - Basconcillo, Joseph; Moon, Il-Ju; Wang, Bin; Mistry, Malcolm
Abstract: In a globally changing climate, there is a growing concern for understanding and predicting compound climate extremes. However, the relationship of compound climate extremes with each other has been mostly analyzed in isolation and/or on regional scales. Little attention has been paid to their simultaneous occurrence and compound impacts worldwide. Here we demonstrate that the compound climate extremes in the Northern Hemisphere during the boreal summer are interconnected from the tropics to the Arctic. This connection originates from the interannual variations of the Indo-Pacific warm pool's intertropical convergence zone (ITCZ). We demonstrate that the warm pool ITCZ (WPI) convection possibly influences three major teleconnection patterns (i.e. zonal, meridional, and circumglobal) where compound climate extremes occur along the wave train excited by the WPI convection. Most notably, the WPI can sufficiently explain climate variabilities in the North Atlantic region, which influences the occurrence of compound climate extremes in many parts of Europe and North America. Our findings advance the understanding of the interannual global/regional variability of climate extremes and are potentially valuable for predicting seasonal high-impact climate extremes.